Genetic markers for the identification of hybrids among catfish species of the family Pimelodidae. (20th January 2013) - Porto‐Foresti, F.; Hashimoto, D. T.; Prado, F. D.; Senhorini, J. A.; Foresti, F.
Summary Fish hybrids provide genetically manipulated products of excellent value for the commercial aquaculture industry. However, if handled or marketed incorrectly, they can cause great financial loss to producers as well as threaten the native species. Herein, molecular markers are established to identify hybrid lineages of pimelodids and characterize them in relation to their parental species, Pseudoplatystoma corruscans, Pseudoplatystoma reticulatum, Phractocephalus hemioliopterus and Leiarius marmoratus. The results show that the mitochondrial genes are useful for identification of the cross‐direction through the characterization of the maternal lineage. The nuclear genes allow identification of the interspecific hybrids. Use of genetic markers can avoid misidentification of hybrids that occur in simple morphological analysis. Thus, the present results allow the routine monitoring of pimelodid hybrids for their correct management and trade in aquaculture.